Design of Time Out Devices for Amateur Volleyball Games Using ESP32 Microcontroller - Bonardo, Doli; Kusuma, Hollanda Arief; Hofur, Viki Dima; Yunianto, Anton Hekso (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study presents the development of a wireless time-out device for amateur volleyball games, utilizing ESP32 microcontrollers and ESP-NOW communication. The device aims to improve the efficiency and accuracy of time-out requests, eliminating delays caused by traditional manual signaling. The functional and field tests confirmed that the device enables seamless communication between coaches and referees, ensuring that time-out requests are processed promptly. Performance evaluations included TFT display readability, push button responsiveness, and communication stability over different distances. The TFT screen demonstrated clear visibility at night but faced readability issues under direct sunlight, suggesting the need for brightness optimization. The distance test showed reliable ESP-NOW communication within a 20-100 meter range, with signal degradation and packet loss beyond this threshold. These findings emphasize the importance of optimizing system placement and display readability to enhance usability in various match conditions. This research provides a practical, cost-effective solution for time-out management in volleyball games. Future improvements may include real-time game analytics, mobile app connectivity, and expanded application to other sports. By addressing key challenges in referee-coach communication, this device contributes to the advancement of sports officiating technology.